Assessing the backlash and pushback to the Supreme Court of Kenya decision in NGO Coordination Board v Gitari and others - Viljoen, Frans (University of Pretoria, 2025)
Mini Dissertation (LLM (Sexual and Reproductive Rights in Africa))-University of Pretoria, 2024.